2015
DOI: 10.1039/c4gc01566e
|View full text |Cite
|
Sign up to set email alerts
|

Facile control of copper nanowire dimensions via the Maillard reaction: using food chemistry for fabricating large-scale transparent flexible conductors

Abstract: Copper nanowires synthesized via Maillard's reaction were sprayed onto various substrates to fabricate flexible conductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 21 publications
0
56
0
1
Order By: Relevance
“…It is well known that the growth mechanism of Cu NWs involves the capping of the HDA molecules toward the {100} facet of the Cu crystal due to an excellent selectivity over the {111} facet, followed by the reduction of Cu 2+ ions into Cu 0 clusters with the use of a mild reductant (glucose). The amount of capping agent is known to significantly affect the resulting shape of the Cu nanocrystals to produce NWs, nanorods, or nanocubes . Therefore, secondary capping agents or shape modifiers are introduced to control the structure of metallic nanomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the growth mechanism of Cu NWs involves the capping of the HDA molecules toward the {100} facet of the Cu crystal due to an excellent selectivity over the {111} facet, followed by the reduction of Cu 2+ ions into Cu 0 clusters with the use of a mild reductant (glucose). The amount of capping agent is known to significantly affect the resulting shape of the Cu nanocrystals to produce NWs, nanorods, or nanocubes . Therefore, secondary capping agents or shape modifiers are introduced to control the structure of metallic nanomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…2f after the reaction [54]. It was found that glucose alone could not reduce Cu ions to metallic Cu, and rather a Maillard reaction took place between alkylamines and glucose and that this reaction was necessary to produce the reductones which in turn reduced Cu ion complexes [54,63]. This reaction was further optimized for the scale up using an in-situ seed-mediated two-step strategy to synthesize well-defined CuNWs in high yield, which was 2.4 times higher than that of the conventional methods with the assistance of Cu nanodots formed in the seeding step.…”
Section: Copper Nanowiresmentioning
confidence: 99%
“…The ink preparetion is therefore important to allow a uniform deposition of copper nanomaterial assemblies. Solvents, such as isopropanol (IPA), ethanol, hexane, or toluene, are used to improve the dispersion stability [63,85,[89][90][91][92][93][94]. The Cu content can range from 0.6 to 1.2 mg mL −1 in the inks [91].…”
Section: Spray Coatingmentioning
confidence: 99%
“….CuNWs の量産化のための水熱合成 では,アミン有機物が重要な役割を果たすことが知られてい る.CuNWs の成長については,アミンが銅核の特定の結晶 面を覆うことで,残された結晶面に沿って一方向に成長する と言われており,アミンが粒子の成長方向を制御する重要な 役割を果たすと考えられている [16][17][18]…”
unclassified